The solvent-induced isomerization of silver thiolate clusters with symmetry transformation. Issue 25 (28th February 2020) - Chen, Xu-Ran; Yang, Ling; Tan, Yu-Ling; Yu, Hong; Ni, Chun-Yan; Niu, Zheng; Lang, Jian-Ping
Abstract : The solvent-induced isomerizations of Ag12 clusters with symmetry transformations were realized by changing the coordinated solvent molecules at room temperature. Abstract : A novel ligand-stabilized Ag12 nanocluster was synthesized as a model cluster to investigate the solvent-induced isomerization of Ag12 clusters. Another two novel Ag12 clusters as well as their related symmetry transformations were also successfully obtained through the above solvent-induced isomerization process.